Europejska Konwencja Bioetyczna w ochronie (bio)bezpieczeństwa człowieka w obszarze biomedycyny: wymiar jednostkowy i społeczny - Mariusz Ciszek (Studia Ecologiae et Bioethicae)
The article presents the essence of biosafety. It was noticed that biosafety was related to three basic dimensions of threats to human safety connected with biotechnological products. They are genetically modified organisms (GMO), the use of biological weapons, and the development of biomedical disciplines. Currently, the greatest threats to human safety are posed by issues related to rapidly developing biomedicine. Those particular threats were introduced on the basis of the analysis of the Convention on Human Rights and Biomedicine, which constitutes the principal bioethical and legal standard protecting human safety and rights within this area, not only in an individual, but also wider, social, and even species dimensions. The issues discussed in the article concern both the selected, "traditional' problems of ethical and legal nature visible within the area of study, and the newest threats related to medicine's interference in the very foundations of the passing down and development of human life. Among others, this concerns eugenic practices, which could make use of genetic engineering. These practices have aroused the most considerable reservations of a moral nature, which demand proper legal regulations protecting human well-being and anticipate possible problems in the near future. An example of these regulations is the above-mentioned Convention on Human Rights and Biomedicine that provides safety measures to Europeans within the area of rapidly developing biomedicine.